Couple relationships in adults with autistic spectrum diagnosis - Bendezú Santisteban, Judith (2025)
This qualitative study, using a phenomenological design, aimed to explore the characteristics of romantic relationships in adults diagnosed with autism spectrum disorder (ASD) in Peru, based on Sternberg’s (1988) triangular theory of love. Seven individuals, of both sexes, aged between 20 and 60 years, were interviewed using a convenience sampling method. A semi-structured interview, validated by expert judges, was conducted with each participant. The results were analyzed using thematic content analysis with the support of Atlas.ti 23 software.The study concluded that the interest of autistic individuals in forming romantic relationships is similar to that of their neurotypical peers, often showing even greater intensity and commitment. Thus, the difficulty in maintaining an emotional bond does not lie in their capacity to feel, but rather in processing social information and in the couple’s adaptive ability to adjust to the relationship.